Physical and physiological characteristics in male team handball players by playing position - Does age matter? - Nikolaidis, P. T.; Ingebrigtsen, J.; Póvoas, S. C.; Moss, S.; Torres-Luque, G. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The purpose of this study was to examine the variation in physical and physiological characteristics according to playing position in adolescent and adult male team handball (TH) players.